Leakage current, ferroelectric and structural properties in Pb(1-x)Ba(x)TiO(3) thin films prepared by chemical route - Pontes, Fenelon Martinho Lima [UNESP]; Santos, L. S. [UNESP]; Rissato, S. R. [UNESP]; Pontes, D. S. L. [UNESP]; Longo, Elson [UNESP]; Leite, E. R.; Claro Neto, S.; Chiquito, A. J.; Pizani, P. S. (Pergamon-Elsevier B.V. Ltd, 2008)
Single-phase perovskite structure Pb(1-x)Ba(x)TiO(3) thin films (x = 0.30, 0.50 and 0.70) were deposited on Pt/Ti/SiO(2)/Si substrates by the spin-coating technique. The dielectric study reveals that the thin films undergo a diffuse type ferroelectric phase transition, which shows a broad peak. An increase of the diffusivity degree with the increasing Barium contents was observed, and it was associated to a grain decrease in the studied composition range. The temperature dependence of the phonon frequencies was used to characterize the phase transition temperatures. Raman modes persist above tetragonal to cubic phase transition temperature, although all optical modes should be Raman inactive. The origin of these modes was interpreted in terms of breakdown of the local cubic symmetry by chemical disorder. The absence of a well-defined transition temperature and the presence of broad bands in some interval temperature above FE-PE phase transition temperature Suggested a diffuse type phase transition. This result corroborates the dielectric constant versus temperature data, which showed a broad ferroelectric phase transition in these thin films. The leakage Current density of the PBT thin films was studied at different temperatures and the data follow the Schottky emission model. Through this analysis the Schottky barrier height values 0.75, 0.53 and 0.34 eV were obtained to the PBT70, PBT50 and PBT30 thin films, respectively. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Thin films; Chemical synthesis; Electrical properties; Phase transition